2018
DOI: 10.3892/or.2018.6447
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between HGF/c-Met and Notch1 signaling pathways in human gastric cancer cells

Abstract: In recent decades, research concerning gastric carcinogenesis has rapidly progressed. It is evident that hepatocyte growth factor (HGF) is clinically related to gastric cancer progression and metastasis. In addition, previous studies have found that expression of Notch ligand Jagged1 is correlated with the poor prognosis of gastric cancer. However, the interaction between the HGF/c-Met and Notch1 signaling pathways remains unknown. In the present study, we found that gastric cancer patients with positive c-Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Data from subgroup analysis related to method, race, tumor stage and type of aberration (amplification or expression) suggested that elevated MET expression had a significant negative impact on survival [73,74]. More recent published reports have confirmed these earlier findings [52,86,103,104].…”
Section: Ii-a-4-gastric Cancermentioning
confidence: 79%
“…Data from subgroup analysis related to method, race, tumor stage and type of aberration (amplification or expression) suggested that elevated MET expression had a significant negative impact on survival [73,74]. More recent published reports have confirmed these earlier findings [52,86,103,104].…”
Section: Ii-a-4-gastric Cancermentioning
confidence: 79%
“…The promotion of astrocyte de‐differentiation by MSC was associated with a reduced expression of the Notch target gene Hes1 , suggesting that soluble factors released by MSC may impair activation of Notch pathway in astrocytes, thereby favoring neural stem cell activities (Magnusson et al, 2014). In this context, a negative feedback loop was recently demonstrated between hepatocyte growth factor (HGF), a soluble mediator of the remyelinating effect of MSC in EAE (Bai et al, 2012), and Notch pathway (Huang et al, 2018), suggesting that MSC could promote de‐differentiation of reactive astrocytes through the HGF‐dependent inhibition of Notch signaling in astrocytes. Accordingly, inhibition of Notch pathway has been demonstrated to alleviate EAE and promote remyelination (Bassil et al, 2011; Hammond et al, 2014), thus pointing to Notch as a possible candidate pathway for the implication of MSC in therapeutic modulation of astrocyte properties.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that COX-2 and Notch knockdown or inhibitors may play a role in the therapeutic strategy against HGF/ c-MET pathway. 37,38 Targeted Therapy Against MET Pathway in GC…”
Section: -Kinase (Pi3k)/akt Extracellular Signal-regulated Kinase (Ementioning
confidence: 99%